Enteroendocrine cells wire the gut–brain vagal axis - Alexander Runyon; Peizhao Zhang; Andy J. Fischer; Michael L. Nonet; Christina Lillesaar; Lihua Ye (Proceedings of the National Academy of Sciences, 2026)
The vagal sensory nervous system plays important roles in mediating gut–brain communication and maintaining physiological homeostasis. Although recent research has greatly enhanced our understanding of the function of vagal sensory neurons, little is known about what guides the vagal sensory nerve fibers to innervate the intestine and form a complex gut–brain sensory network. Here, using zebrafish genetic models to trace the development of the intestinal vagal network, we found that the development of the intestinal vagal sensory network is coupled with the formation of enteroendocrine cells (EECs). Vagal sensory neurons begin to innervate the intestine at 2 d postfertilization. Vagal nerve fibers branch out toward the newly formed EECs in the intestinal epithelium. The newly formed EECs display active actin filaments at their base, enabling them to physically engage with the vagal sensory fibers and facilitate the formation of the intestinal vagal sensory network. Genetically ablating EECs impairs intestinal vagal network formation and alters the vagal central projection pattern. Ablating EECs induces apoptosis in a subset of vagal sensory neurons and reduces the number of central projecting axons of the intestine innervating vagal sensory neurons. Moreover, ablating EECs completely alters the brain’s response to nutrient ingestion and diminishes nutrient-induced hindbrain and hypothalamus neuron activation. Finally, loss of EECs increases food intake while impairing adipose tissue development and survival. Together, our study revealed that EECs guide vagal sensory neuron development and intestinal vagal network formation. Loss of EECs impairs the anatomical vagal sensory axis and alters gut–brain signaling transmission.